The Logos of the Living World : Merleau-Ponty, Animals, and Language - Westling, Louise Hutchings (Book collections on Project MUSE., 2014)
This is an interdisciplinary work that puts Maurice Merleau-Ponty's philosophy into dialogue with evolutionary biology, animal studies, and literature, arguing for evolutionary continuity between human cultural and linguistic behaviours and the semiotic activities of other animals. Differing from other studies of Merleau-Ponty's work, this book emphasises his lifelong attention to science, showing how his examination of evolutionary biology, embryology, and ethology anticipated studies of animal behaviour, cognition, and communication.